Pertumbuhan Penjualan, Struktur Aset dan Struktur Modal - Asmara, Eka Noor; Kusumadewi, Hermala; Ashari, Sidiq; Djasmanuddin, Djasmanuddin (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
The research objective was to determine the effect of sales growth and asset structure on capital structure in manufacturing industry companies. The data used in this research is secondary data in financial reports. The sampling technique in this study used purposive sampling. The number of samples that match the criteria is 100 manufacturing industry companies with the 2016-2020 research period. Sales growth is measured by comparing sales in year t after deducting sales in the previous period to sales in the previous period, asset structure is measured by the fixed assets ratio, and capital structure is measured by the debt ratio. The analytical tool used is multiple linear regression. The results showed that sales growth had no significant effect on capital structure, while asset structure had a significant effect on capital structure in manufacturing industry companies. Keywords: Sales growth; Assets Structure; Capital Structure.